STUDI KASUS TENTANG SISWA YANG MUDAH MARAH DAMPAK DARI BROKEN HOME DI SMA - Februari, Ankgah; Yuline, Yuline; Purwanti, Purwanti (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis thesis entitled "Case Study of Students who are Easily Angry Impact of Broken Home in SMAN 5 Pontianak". Common Problem in this research: "How to effort to alleviate students easily angry impact of broken home in SMAN 5 Pontianak?". As for the sub-problems: 1) How are the characteristics of students easily angry the impact of broken home in SMAN 5 Pontianak ?, 2) What factors cause students to easily anger the impact of broken home in SMAN 5 Pontianak ?, 3) What alternative assistance is appropriate to address students the irritable impact of broken home in SMAN 5 Pontianak ?. This study aims to reveal students easily angered the impact of broken home in SMAN 5 Pontianak. The approach used in this research is qualitative by using descriptive method. The form of research used is case study (case study). Data collecting techniques include direct observation, direct interview, home visit, and documentation. Based on the results of observations and interviews concluded the characteristics of students who have the nature of irritability that is often said roughly to berate his friend. The alternative assistance provided is to use the REBT and behavioral counseling approach with confrontation techniques and assertive techniques. The results of the case study after being given help has been shown to indicate a change towards the better.Â Keywords : student, easily angry, broken homeÂ